New product development resource forecasting. (12th May 2015) - Hird, Abigail; Mendibil, Kepa; Duffy, Alex; Whitfield, Robert Ian
Abstract : Forecasting resource requirements for new product development (NPD) projects is essential for both strategic and tactical planning. Sophisticated, elegant planning tools to present data and inform decision‐making do exist. However, in NPD, such tools run on unreliable, estimation‐based resource information derived through undefined processes. This paper establishes that existing methods do not provide transparent, consistent, timely or accurate resource planning information, highlighting the need for a new approach to resource forecasting, specifically in the field of NPD. The gap between the practical issues and available methods highlights the possibility of developing a novel design of experiments approach to create resource forecasting models.